2014
DOI: 10.1021/pr500656z
|View full text |Cite
|
Sign up to set email alerts
|

Dysbindin-Associated Proteome in the P2 Synaptosome Fraction of Mouse Brain

Abstract: The gene DTNBP1 encodes the protein dysbindin and is among the most promising and highly investigated schizophrenia-risk genes. Accumulating evidence suggests that dysbindin plays an important role in the regulation of neuroplasticity. Dysbindin was reported to be a stable component of BLOC-1 complex in the cytosol. However, little is known about the endogenous dysbindin-containing complex in the brain synaptosome. In this study, we investigated the associated proteome of dysbindin in the P2 synaptosome fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 72 publications
(186 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, high levels of WDR11 are found in the brains of embryonic and adult mice (35), and disruptions to WDR11 are associated with IHH/KS/CPHD (35,38), conditions that result from abnormal migration of specific neurons during embryogenesis (reviewed in reference 101). Additionally, WDR11 interacts with dysbindin, a neuronal protein enriched in synapses (102), as well as EMX1 (35), a protein with important functions in the developing nervous system (reviewed in reference 103). Therefore, it is possible that the function of WDR11 may be more crucial for viral replication in vivo in neurons as opposed to cells of the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high levels of WDR11 are found in the brains of embryonic and adult mice (35), and disruptions to WDR11 are associated with IHH/KS/CPHD (35,38), conditions that result from abnormal migration of specific neurons during embryogenesis (reviewed in reference 101). Additionally, WDR11 interacts with dysbindin, a neuronal protein enriched in synapses (102), as well as EMX1 (35), a protein with important functions in the developing nervous system (reviewed in reference 103). Therefore, it is possible that the function of WDR11 may be more crucial for viral replication in vivo in neurons as opposed to cells of the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…Annotation of these proteins to neuronal functions indicates that in a majority they are involved in neurotransmitter vesicle fusion and synaptic plasticity [ 102 ]. Additional quantitative proteomic studies have identified changes in expression of proteins and polypeptides sensitive to dysbindin/BLOC-1 loss of function, including: (i) the BLOC-1 subunits, such as Bloc1s1-5 and snapin; (ii) dynactin complex, such as alpha-centractin and dynactin 2; (iii) exocyst complex, such as exocyst 3 and exocyst 4; (iv) tubulin/actin associated proteins, such as actin alpha 1 and tubulin alpha 1b; (v) AP3 complex, such as adaptor-related protein complex-3B1 and -2; (vi) vesicular transport/trafficking associated/fusion apparatus, such as adaptor protein 2A1, the vesicle associated membrane protein 7, syntaxin-binding protein 1 and 5; (vii) proteasome subunits, such as proteasome modulator 9 and proteasome subunit alpha type 4; and (viii) other proteins, such as the copper-transporting P-type adenosine triphosphatase (ATP7A), the N -ethymaleimide-sensitive factor, annexin A2, syntaxin 7 and 17, synaptosomal-associated protein 25 and family with sequence similarity 91 member A1 [ 95 , 98 , 102 , 103 , 104 ]. Future investigations on these dysbindin-1-interacting proteins are expected to expand dysbindin-1 neuronal functions and provide alternative, additional molecular targets for schizophrenia susceptibility.…”
Section: Dysbindin-1 Is Required For Diverse Presynaptic and Postsmentioning
confidence: 99%
“…The proteasome is essential for the development and function of numerous organs and structures of the human body [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. Thus, reduced activity of the cilia-regulated proteasome is a possible cause of ciliopathies.…”
Section: The Cilia-regulated Proteasome Is Essential For Gli Procementioning
confidence: 99%